Use of social networking sites and perception and intentions regarding body weight among adolescents - H. Sampasa‐Kanyinga; J.‐P. Chaput; H. A. Hamilton (Wiley, 2016)
Summary Objective Social networking sites (SNSs) not only offer users an opportunity to link with others but also allow individuals to compare themselves with other users. However, the link between the use of SNSs and the dissatisfaction with body weight is largely unknown. We investigated the associations between the use of SNSs and the perception of body weight and related behaviours among adolescent men and women. Methods The study sample consisted of 4,468 (48.5% women) 11-19‐year‐old Canadian students in grades 7 to 12 who participated in the 2013 Ontario Student Drug Use and Health Survey. Results Overall, 54.6% of students reported using SNSs for 2 h or less per day, 28.0% reported using them for more than 2 h d−1 and 17.4% reported infrequent or no use of SNSs (reference category). After adjustment for covariates, results showed that adolescent women who use SNSs for more than 2 h d−1 had greater odds of dissatisfaction with body weight (odds ratio = 2.02; 95% confidence interval [CI]: 1.30-3.16). More specifically, they were more likely to perceive themselves as overweight (relative risk ratio [RRR] = 2.20; 95% CI: 1.34−3.60) compared with those who reported infrequent or no use of SNSs. Conversely, men who use SNSs for 2 h or less per day presented a lower risk for perceiving themselves as overweight (RRR = 0.68; 95% CI: 0.47−0.98) but not those who use SNSs for more than 2 h d−1. Women who use SNSs for more than 2 h d−1 reported a greater likelihood of trying to lose weight (RRR = 2.52; 95% CI: 1.62−3.90). Conclusions Our results showed that heavy use of SNSs is associated with dissatisfaction with body weight in adolescent women.